The Effectiveness of Black Seed Extract (Nigella Sativa) on the Movement of Ascaridia Galli Worms in Vitro - Rahmat Sabir; Santriani Hadi; Mona Nulanda; Nurfachanti Fattah; Andi Alamanda Irwan (Journal La Medihealtico, 2026)
This study concludes that Black Seed (Nigella sativa) extract demonstrates significant anthelmintic activity against Ascaridia galli in vitro, as evidenced by decreased worm motility and reduced time to death across treatment groups. The findings highlight a clear dose–response relationship, where higher extract concentrations produce stronger and faster anthelmintic effects. Statistical analyses, including the Friedman test and One-Way ANOVA, confirm that most treatment groups show significant differences in worm motility and mortality compared to the negative control, while the highest concentration (100%) exhibits effectiveness comparable to the positive control (pyrantel pamoate). The presence of bioactive compounds such as alkaloids, flavonoids, saponins, tannins, and triterpenoids further supports the biological mechanism underlying this effect, particularly through pathways involving neuromuscular disruption, protein denaturation, and inhibition of energy metabolism in worms. Overall, these results indicate that Black Seed extract has strong potential as a natural alternative anthelmintic agent, although further in vivo studies and clinical validation are required to confirm its safety, efficacy, and practical application in both veterinary and human health contexts